2019
DOI: 10.1155/2019/5431354
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Effect ofBacillus amyloliquefaciensTL on Cecal Bacterial Community Structure of Broiler Chickens

Abstract: Probiotics can promote the health and growth performance of animals through modulation of intestinal microbiota. When used as a feed additive, they have the potential to minimize or abolish the use of antibiotics. In this study, we investigated the effect of the probiotic strain Bacillus amyloliquefaciens TL on the growth performance and cecum microflora composition in Cobb 500 broiler chickens. In total, 180 broilers were randomly divided into three groups—each group comprised 4 pens, and each pen contained 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 61 publications
5
30
0
1
Order By: Relevance
“…The relative abundances of multiple or potential beneficial bacteria were higher at the genus level in the BA and BP groups compared to the control group, including Lactobacillus, Bacillus, Succiniclasticum, unidentified Lachnospiraceae, among others; however, the relative abundances of multiple or potentially pathogenic bacteria were lower in the BA and BP groups compared to the control group, including Pseudomonas, unidentified Enterobacteriaceae, and Klebsiella, among others. These results indicated that feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09 promoted the growth of probiotics and inhibited pathogenic bacteria growth in the digestive tract, which agrees with a previous report related to feeding broiler chickens and grouper (Epinephelus coioides) with Bacillus amyloliquefaciens TL and Bacillus pumilus SE5 respectively [10,28]. It is well accepted that there is an interaction between microbial communities in rumen and caecum.…”
Section: Discussionsupporting
confidence: 90%
“…The relative abundances of multiple or potential beneficial bacteria were higher at the genus level in the BA and BP groups compared to the control group, including Lactobacillus, Bacillus, Succiniclasticum, unidentified Lachnospiraceae, among others; however, the relative abundances of multiple or potentially pathogenic bacteria were lower in the BA and BP groups compared to the control group, including Pseudomonas, unidentified Enterobacteriaceae, and Klebsiella, among others. These results indicated that feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09 promoted the growth of probiotics and inhibited pathogenic bacteria growth in the digestive tract, which agrees with a previous report related to feeding broiler chickens and grouper (Epinephelus coioides) with Bacillus amyloliquefaciens TL and Bacillus pumilus SE5 respectively [10,28]. It is well accepted that there is an interaction between microbial communities in rumen and caecum.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that the jejunal microbiota of chicks supplemented with ciprofloxacin lactate had higher richness and evenness compared to the cCON and cCCAB groups according to the alpha diversity results ( Table 1 ), and the distribution of the Cipro group individuals in NMDS was distant from that of the cCON and cCCAB groups for beta diversity analysis. Therefore, we suggest that the chicks with ciprofloxacin lactate supplementation might lead to higher richness, evenness, and varied microbial structures in jejunums, similar to the results of a recent study reporting that broiler chickens supplemented with an antibiotic (chlortetracycline) showed significantly increased Chao1 and Shannon diversity indices in cecal microbiota after 14 D of treatment ( Hong et al., 2019 ), and a previous study considered antibiotic therapy as a factor that influenced the intestinal microbial composition ( Cisek and Binek, 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…In general, immune system activation is energetically costly, and long-term stimulation can have negative effects on the host [ 24 ]. Our previous study showed that dietary supplementation with Bacillus amyloliquefaciens TL improves the growth of broilers [ 26 ]. We speculated that this phenomenon was due to B. amyloliquefaciens TL, which can alter the gut microbiota and subsequently lower intestinal inflammation and the systemic immune response, diverting more energy toward growth.…”
Section: Introductionmentioning
confidence: 99%